(untitled) (Washington, D.C., 2000)
Cellular Microbiology describes interactions of microbes and pathogens in the wider context of the cell properties, helping the reader to envisage different possibilities for his or her own problem while detailing known specific examples. It provides microbiologists moving into cell biology a deep understanding of the field as well as a broader knowledge of possible interaction between their favorite organism and mammalian cells. It also provides cell biologists with a comprehensive update of this emerging field.
Keywords: Infection,Pathology, Cellular,Bệnh lý, di động,Nhiễm trùng